CHANGES IN SOIL CHEMICAL ATTRIBUTES AND NUTRITION OF Anadenanthera colubrina AND Eucalyptus CLONE UNDER NATURAL FERTILIZERS AND BIOCHAR - Araujo, Emmanoella Costa Guaraná; Silva, José Antônio Aleixo da; Freire, Fernando José; Ferreira, Rinaldo Luiz Caraciolo; Silva, Thiago Cardoso (Floresta, 2021)
This study aimed to evaluate changes in soil chemical attributes and nutrition of Anadenanthera colubrina and a Eucalyptus clone under fertilization using reservoir sediment (RS), fish farming sediment (FFS) and biochar (BC) in the semi-arid region of Brazil. The Eucalyptus clone and A. colubrina leaves and soil were sampled after applying treatments. Leaves were collected for nutritional analysis and soil for mineral and fertility analyses. The K+ and P concentration in the soil were influenced by the natural fertilizers, and the biochar increased the C content. The A. colubrina planting reduced the soil K+ and P levels, and the Eucalyptus clone cultivation reduced the Mg2+ content. The FFS was responsible for increasing P availability in both A. colubrina and the Eucalyptus clone, being a good option for use in soils which are naturally poor in P. A. colubrina presented the highest N, P, K and Ca levels, suggesting high demand of this species for these nutrients. The Eucalyptus clone was more demanding for Mg, suggesting that its cultivation should be done in soils rich in Mg2+. The use of RS and FFS is important to increase the growth of forest species in semi-arid regions, and this management is recommended in the deforestation policies of these regions.